Educational Materials In The Qur'an (Study of Surah Al-'Asr) - Amir HM, HM (oneamd.com, 2024)
The Qur'an is present as a guide and guidance that covers all human needs, one of which is educational material. Surah al-Aṣr is the 103rd surah in the Qur'an consisting of 3 verses. in it there are educational materials that are very relevant to the demands of the times, both in the form of formal, informal, and non-formal education, as well as in education levels, ranging from kindergarten to college. The main content of the surah is; First, time or discipline informed by God in the form of an oath which shows how important it is to pay attention to the use of time or discipline. Second, faith and good deeds must be integrated into human life. Faith without good deeds is meaningless, righteous deeds without faith are blind. Third, remind each other about truth and patience. Fourth, the main content of the surah should be part of the educational material that must be programmed systematically and structured so that it becomes an inseparable part of managing education